A Cleveland model? - Alessandro Coppola (Métropoles)
The paper argues that the case of the city of Cleveland offers three main examples of alternative recent urban development practices that are deeply rooted in the context of persistent urban shrinkage: 1) the establishment of a county land-bank aimed at assembling unused land in order to repurpose it also in the direction of “alternative land uses” such as urban agriculture and ecological restoration; 2) the design of a program – the “Reimagining a more sustainable Cleveland” initiative – aimed at implementing innovative greening strategies through the activation of local residents and communities; 3) the consistent investment of local philanthropic institutions in new economic development efforts aimed at establishing local cooperatives operating on a local market also but not exclusively focusing on “green economy” products and services. Following the description and discussion of these practices, the paper argues that the case of Cleveland represents a consistent shift from previous neoliberal urban development models that have been widely implemented across the urban Rustbelt of the United States. The main elements of this new approach are: 1) a new treatment of the physical footprint of the city that is consistently coherent with the “smart-shrinkage” and “rightsizing” literatures; 2) the acceptance of the return of part of the land to its use-value and away from commodification circuits; 3) the reconsideration of the priority of real-estate development on behalf of the “Community development industry” through the formulation on a more diverse set of policies and programs; 4) the investment of important city actors in alternative economic development models aimed at re-localizing the economy; 5) the increasing relevance of targets of social and environmental sustainability in the expansion of alternative food production and distribution systems.